(untitled) (Physical Education, Health and Social Sciences, 2025)
Increasingly, burnout is seen in bosoth the academic and practical fields. Academicians may also experience burnout differently depending on where they work. Service and health sector burnout has been studied extensively, but education has received less attention. In order to predict burnout, the main predictor is emotional exhaustion. Excessive work pressure, personal demands, or accumulated stress can cause emotional exhaustion. A feeling of mental exhaustion caused by social interactions. This study aims to determine how emotional exhaustion affects academicians’ workload and organizational commitment in Malakand division. In order to collect the data from 212 academicians, a cross-sectional method was used, and a variety of statistical tools were used to analyze the data. Workload correlates positively with emotional exhaustion, while organizational commitment correlates negatively. In organizational commitment and workload, emotional exhaustion is a mediating factor. As a result of this study, academicians will have a better understanding of how they interact and to what extent their emotions directly impact their organizational commitment. Results of the study were addressed to students, academicians, administration of universities and policymakers in higher education.